School modality, race and ethnicity, and mental health of U.S. adolescents during the COVID-19 pandemic - Vijaya Tamla Rai; Linnea Irina Laestadius; Celeste Campos-Castillo (BMC, 2024)
Abstract Background While minoritized ethnoracial groups were most likely to be in online learning during the COVID-19 pandemic, the impact of these ethnoracial disparities on adolescent mental health is unclear. Since past studies do not directly examine whether the association between school modality and self-reported mental health outcomes varied by race and ethnicity among U.S. adolescents during the COVID-19 pandemic, this study addresses the gap. Methods Adolescents aged 13 to 17 years old (n = 510) were surveyed for self-reports of anxiety and depression symptoms using the 4-item Patient Health Questionnaire during Spring 2021. Seemingly unrelated regressions were used to estimate the differential association between school modality and mental health by respondents' race and ethnicity. Results Estimates without interaction between school modality and race and ethnicity suggested that Latino respondents reported a significantly higher frequency of depressive symptoms than their White counterparts (b = 0.459; p < 0.05). Similarly, the estimates without the interaction suggested respondents reporting hybrid learning had a higher frequency of depressive symptoms than in-person learning (b = 0.504; p < 0.05). Estimates with interaction between school modality and race and ethnicity suggested fully online learning was associated with poorer mental health only among White respondents and better mental health among Black respondents. Among adolescents attending school fully online, Black adolescents reported fewer mental health symptoms than their White counterparts (anxiety, b =- 1.364; p < 0.05, and depression, b =- 1.647; p < 0.05). Conclusions Fully online learning may have benefitted the mental health of Black adolescents during the COVID-19 pandemic, perhaps because it buffered racial discrimination and social anxiety in schools. Additional interventions should be explored to promote in-person school environments that better support the mental health of Black adolescents. Moreover, prioritizing equitable access to broadband internet will provide better access to online learning and ensure positive mental health, particularly for adolescents from minoritized ethnoracial groups during instances of future pandemics. Future research should continue to consider the race and ethnicity of adolescents to promote mental well-being in schools across learning modalities.